The influence of media literacy on students' social protection in adult and vocational education policy in Rivers State, Nigeria - Olori, Christian; Ewuru, Agnes; Omang, Theresa; Olori, Gloria; Okanazu, Oliver; Nwizu, Stella; Ogu, Bala (Department of Government Studies Universitas Muhammadiyah Makassar, 2025)
This study examines the effect of media literacy on students' social protection in adult and vocational education policy in Rivers State, Nigeria, based on experiences from the COVID-19 pandemic. The following three research questions and corresponding null hypotheses were formulated. A quasi-experimental design with an experimental group and a control group was used. A sample of 180 learners was randomly selected from a total of 2,378 adult learners in six adult literacy centers. The data collection instrument used in this study was the Learners Social Protection Test (LeSPT), which was developed by the researchers and tested for face and content validity by three experts. A reliability coefficient of 0.87 was obtained through the application of the Kuder-Richardson formula (K-R20). The data collected were analyzed using mean, standard deviation, and analysis of covariance. Findings indicated that students who received media literacy instruction showed significantly greater positive effects on social protection compared to students who only received basic literacy instruction.